2022
DOI: 10.3390/ijerph191610026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Immediate Impact of Graphic Messages for Vaping Prevention among Black and Latino Adolescents: A Randomized Controlled Trial

Abstract: The purpose of this pilot study was to assess the immediate impact of vaping prevention graphic messages on the susceptibility to future vaping among Black and Latino adolescents (ages 12 to 17). Graphic messages (available in English and Spanish) were developed using participatory research procedures with Black and Latino adolescents. Recruitment was conducted by a team of diverse, bilingual (English and Spanish), trained recruiters. Participants (n = 362) were randomized in a 1:1:1:1 schema to receive one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This study is a secondary data analysis of a randomized controlled trial (RCT) designed to assess the immediate impact of vaping prevention graphic messages on the susceptibility of future vaping among Black and Latino adolescents ( 11 , 12 ). The RCT purposely focused on Black and Latino adolescents given their underrepresentation in previous vaping prevention studies ( 12 ). Details and results of the RCT have been reported elsewhere ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a secondary data analysis of a randomized controlled trial (RCT) designed to assess the immediate impact of vaping prevention graphic messages on the susceptibility of future vaping among Black and Latino adolescents ( 11 , 12 ). The RCT purposely focused on Black and Latino adolescents given their underrepresentation in previous vaping prevention studies ( 12 ). Details and results of the RCT have been reported elsewhere ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…The RCT purposely focused on Black and Latino adolescents given their underrepresentation in previous vaping prevention studies ( 12 ). Details and results of the RCT have been reported elsewhere ( 12 ). The RCT was approved and monitored by the University of Rochester Medical Center Institutional Review Board (STUDY00006267).…”
Section: Methodsmentioning
confidence: 99%
“…Emergent literature has demonstrated that susceptibility to e-cigarettes, defined as the absence of a firm decision not to use e-cigarettes, is a strong independent predictor of future vaping 3 - 5 . Moreover, susceptibility to e-cigarettes has been proposed as an outcome for vaping prevention efforts 6 .…”
mentioning
confidence: 99%
“…Data are from a randomized controlled trial to assess the immediate impact of vaping prevention graphic messages among 362 Black and Latino adolescents (aged 12–17 years), with equal representation between the two groups 6 - 7 . The study design and results are described thoroughly in a previous publication 6 . A forward-backward methodology was used to translate the susceptibility to e-cigarettes scale into Spanish 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation